Pathways less travelled to value creation : interaction, dialogue and knowledge generation - Ballantyne, David (Journal of business & industrial marketing, 2004)
Relationship marketing is based on the idea that the existence of a relationship between customer and supplier creates value for both parties, in addition to the value of the products or services provided. In this special issue edition entitled "Pathways less traveled to value creation: interaction, dialogue and knowledge generation" articles are submitted from five sets of authors, giving different perspectives of marketing and the knowledge generation and communication aspects surrounding it.